Seeing Like a Citizen: Exploring Public Views of Biometrics. (May 2019) - Norval, Aletta; Prasopoulou, Elpida
Despite its controversial history and significant diffusion of biometrics from institutional settings such as border control and policing to everyday use in commerce and personal devices, biometrics is now being re-positioned as a neutral means to safeguard identity in the digital world. Given this proliferation of uses, we argue that understanding perceptions of biometrics among ordinary citizens is necessary and long overdue. Situating our analysis in the wider context of the views of government and biometric industry experts, we deploy Q-methodology in combination with political discourse analysis to examine the range of positions that have crystallized in ordinary discourse on issues arising from the use of biometrics for identification. Our analysis uncovers four distinctive configurations that put into question a simplistic trade-off between security and privacy that dominates government and industry discourse and underlines the importance of going beyond a narrow view of technology 'users' to understand the political and social concerns that arise with and shape the uses of technology in contemporary society.